Fashion Business Sustainability for Fashion Designers in the Indonesian Fashion Industry - Nadia Putri Agusalim (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
The fashion industry remains as one of the most highly competitive industries where many fashion designers may find it difficult to establish sustainable fashion businesses. Navigating through the fashion business and ensuring business success, growth and long-term sustainability were generally considered to be the ultimate goal and biggest challenge many fashion designers continue to struggle with. This study was aimed to determine all key factors that are integral and contribute to fashion business sustainability by presenting findings provided by three Indonesian fashion designer’s responses to the issue of fashion business sustainability, the various challenges, and what factors are needed to ensure a long lasting through semi-structured in-depth interviews. Overall findings revealed the need for fashion designers to have an entrepreneurial mindset and for fashion businesses to possess all sustainable business key factors in various aspects ranging from design, business and the various qualities from the fashion designer themselves, while also taking account of the external state which was set in the Indonesian fashion industry for business sustainability and organic business growth. Fashion designers who controls all these factors will have a significantly higher chance of sustainability while competing with other fashion businesses.